Plants mentioned in the Islamic scriptures (Holy Qur'ân and Ahadith): traditional uses and medicinal importance in contemporary times - El-Seedi, Hesham Rushdey; Khalifa, Shaden Ali M.; Nermeen, Yosri; Khatib, Alfi; Lei, Chen; Saeed, Aamer; Efferth, Thomas; Verpoorte, Robert (Elsevier Ireland Ltd, 2019)
Ethnopharmacological relevance Over the past thousand years, Islamic physicians have collected cultural, philosophical, sociological and historical backgrounds for understanding diseases and medications. The Prophet Mohammed (Peace Be Upon Him (PBUH) said: “There is no disease that Allah has created, except that Allah also has created its cure.” Therefore, Islamic scholars are encouraged to explore and use both traditional and modern forms of medicine.